Stepping into Islamic Environmental Sustainability in Indonesia: Developing a Framework for Balancing Economic Growth, Renewable Energy, and Carbon Emissions - Qoyum, Abdul; Prasojo, Prasojo; Bin Mohd Thas Thaker, Hassanudin; Hosen, Mosharrof; Hasanah, Imas (EKONOMIKA SYARIAH : Journal of Economic Studies, 2025)
The growing threat of climate change and environmental degradation has intensified interest in understanding the role of renewable energy in promoting economic growth while reducing carbon dioxide (CO₂) emissions. This study examines the interrelationships among political risk, financial risk, technological innovation, renewable energy consumption, environmental pollution, and CO₂ emissions in the Indonesian context. Secondary data were obtained from reputable sources, including Bloomberg and the World Development Indicators (WDI). To ensure robust empirical analysis, this study employs Wavelet analysis and the Autoregressive Distributed Lag (ARDL) approach to capture both short-run and long-run dynamics. The empirical findings reveal the existence of a long-run cointegrating relationship among the studied variables, indicating that renewable energy, financial conditions, and environmental factors move together toward long-term equilibrium. The long-run results show that financial conditions have a positive and statistically significant impact on carbon emissions, suggesting that financial expansion may intensify environmental pressures if not aligned with sustainable policies. These findings provide important policy implications, highlighting the need to strengthen green finance mechanisms, support renewable energy investments, and promote clean technological innovation to achieve sustainable economic development. The study offers valuable insights for policymakers in designing effective strategies to balance economic growth with environmental sustainability in Indonesia. Ancaman perubahan iklim dan degradasi lingkungan yang semakin meningkat telah memperkuat minat dalam memahami peran energi terbarukan dalam mendorong pertumbuhan ekonomi sambil mengurangi emisi karbon dioksida (CO₂). Studi ini menganalisis hubungan timbal balik antara risiko politik, risiko keuangan, inovasi teknologi, konsumsi energi terbarukan, polusi lingkungan, dan emisi CO₂ dalam konteks Indonesia. Data sekunder diperoleh dari sumber-sumber terpercaya, termasuk Bloomberg dan World Development Indicators (WDI). Untuk memastikan analisis empiris yang kokoh, studi ini menggunakan analisis Wavelet dan pendekatan Autoregressive Distributed Lag (ARDL) untuk menangkap dinamika jangka pendek dan jangka panjang. Temuan empiris menunjukkan adanya hubungan kointegrasi jangka panjang di antara variabel yang diteliti, menunjukkan bahwa energi terbarukan, kondisi keuangan, dan faktor lingkungan bergerak bersama menuju keseimbangan jangka panjang. Hasil jangka panjang menunjukkan bahwa kondisi keuangan memiliki dampak positif dan secara statistik signifikan terhadap emisi karbon, menyarankan bahwa ekspansi keuangan dapat memperburuk tekanan lingkungan jika tidak sejalan dengan kebijakan berkelanjutan. Temuan ini memberikan implikasi kebijakan yang penting, menyoroti perlunya memperkuat mekanisme keuangan hijau, mendukung investasi energi terbarukan, dan mempromosikan inovasi teknologi bersih untuk mencapai pembangunan ekonomi berkelanjutan. Studi ini memberikan wawasan berharga bagi pembuat kebijakan dalam merancang strategi efektif untuk menyeimbangkan pertumbuhan ekonomi dengan keberlanjutan lingkungan di Indonesia.